The action of a laser on an aluminium target - Henč-Bartolič, Višnja (Materiali in tehnologije, 2008)
A nitrogen laser beam (337 nm, 6 ns (FWHM), (3.2 plus minus 0.2) mJ) was focused with a quartz lens (f = 100 mm) onto an aluminium target in air at normal pressure. The laser irradiation and plasma explosion caused a modification to the Al surface and the deposition of a thin film (droplets) onto a glassy carbon plate. The irradiated target and the deposited material were studied with a scanning electron microscope (SEM) and a focused-ion-beam (FIB) device. A crater surrounded by a rim was produced on the spot of maximum irradiation on the aluminium target. The crater, very deep in comparison to its width and thickness, was presumably caused by the Kelvin-Helmholtz and the Rayleigh-Taylor instabilities. The temperatures of the electron and the massive particles were explained.
Keywords: aluminij; Aluminij Mostar; aluminum; laserska ablacija; tanke plasti; preiskava materiala